Genetic Analysis Reveals A Missense Mutation In Reactivation Gene-2 Causing Severe Combined Immunodeficiency Disease In A Pakistani Family: Missense mutation in RAG2 gene causing SCID - Awais, Shahida; Siddique , Lubna; Shafi, Nida; Humerah, Sobia; Niazi, Summyah; Omer, Wafa (Journal of Rawalpindi Medical College, 2024)
Abstract Objective: To perform clinical and genetic analysis in a patient suffering from lymphopenia (low B-lymphocyte, T-lymphocyte and healthy Natural Killer cells). Methodology: In the current research project we enrolled a female child from Rawalpindi district. Laboratory investigations including lymphocyte subset analysis was performed using anti-antibodies (CD19, CD3, CD4, CD8 and CD16/56). Estimation of serum immunoglobulin’s were performed. DNA Sanger sequencing of RAG2 gene was performed to identify gene mutation. Results: Thorough clinical examination by team of expert physician revealed severe nappy rash, interstitial pneumonitis and intractable diarrhea leading to failure to thrive. Lymphopenia with CD3+CD8 cells (0.1%), CD19 cells (0.1%), CD19/CD56 cells (27%) and CD4/CD8 cells (0.0%) resulting in B-T-NK+ deficiency. Patient’s serum immunoglobulin’s showed low levels of IgG, IgA and IgM levels. Exons specific polymerase chain reaction (PCR) was performed using oligonucleotide primers and subsequently DNA Sanger sequenced which resulted into an missense variant in the gene RAG2. Conclusion: In human reactivation gene 1 and 2 encode proteins with endonuclease activity which are involved in V(D)J rearrangement to generate variety of different types of T- and B- cell receptors. Genetic analysis revealed a missense mutation in RAG2 genes in female SCID patient.